A propósito del principio de conservación de la energía: una propuesta de formalización en la enseñanza de la física desde un análisis histórico y epistemológico de la perspectiva de Mayer - Arboleda Correa, Alba Denis; Díaz Valencia, Mónica Xiomara; Aguilar Mosquera, Yirsen (Revista Científica, 2011)
In the analysis done in some researches, shows that some students' difficulties in physics, are closely related to the relationship established between common knowledge and scientific knowledge. Usually, students explain the phenomena from common knowledge, that is, from what they have learnt in their daily life, as a particular case, we can make reference to physical situations that are solved by the application of the Principle of Energy Conservation (Pozo, 2000). In these situations, it is kind of problematic the relationship established between the concepts of work, mass, portability, warmth and strength, among others. In relation to work and energy, the work is conceptualized in terms of energy and energy in terms of work; that means that there is a circularity arised between these two concepts. Also, students assigned a material character to energy,mixed forms of energy with its sources, it is given substantiality to heat and does not take into account processes of transformation, transfer and degradation of energy. With the intention to build some conceptual alternative routes for teaching of the mechanics, it is done a historical epistemological analysis on Mayer’s way, how he sets upand presents the Principle of Energy Conservation, stated in his work named Observationson the energies of inorganic nature (1842). This analysis shows how Mayer establishes the principle of causality as a function (cause = effect = cause), he considers the causes how entities indestructible quantitatively and convertible qualitative lyand from these considerations, he suggests that energies are indestructible and convertible entities.Taking into account these considerations, it is assumed the indestructibility and convertibility as structured Principles in Energy Conservation and they remean the terms of work, power and portability.Finally, from the analysis of the Mayer formalization proposal and explanatory models of five cases of eleventh grade of Institución Educativa Comercial ofEnvigado, it is presented some pedagogical implications which are considered activitiesthat enable on the principle Energy Conservation concepts.